Growth and semen characteristics of West African dwarf rams fed ammonium sulphate supplemented diets (2017)
Ammonium sulphate (AS) is widely used as a feed additive for animals. It is generally used to provide supplemental sulphur to the diet, particularly in diets containing non-protein nitrogen sources. This study assessed the growth and reproductive performance of Yankasa rams fed diets supplemented with different levels of ammonium sulphate. Ammonium sulphate was added at 0, 0.5, 1.0, and 1.5g/kg of the concentrate diet as T0, T0.5, T1.0 and T1.5 respectively. Each treatment had four replicates while semen was collected once from all replicates in the treatments. Rams were fed experimental diets for 70 days. The parameters determined were: feed intake, body weight gain, feed conversion ratio, mass activity, motility, livability, sperm volume, sperm concentration, scrotal circumference and length. There were significant differences in the feed intake, body weight gain and the feed conversion ratio of the West African dwarf rams fed the supplemented diets. The rams fed diet T1.0 had the highest feed intake and body weight gain of 403.75g/day and 195.83g/day respectively above other treatments. The FCR in T1.0 was the lowest at 2.11 below 6.68 (T0) There was significant difference in the sperm concentration (x10(6)spz/ml) with T1.5 (160.25) having the highest while T0 (136.00) had the lowest. The total sperm ejaculate follow the same trend as sperm concentration with the lowest value recorded in T0 (98.95) while T1.5 (151.65) had the highest value. There were no significant differences in the values recorded for the scrotal circumference and length, however, scrotal weight, total testicular weight, scrotal length and scrotal circumference values in T1.5 was numerically higher than other treatments. It can be concluded that inclusion of ammonium sulphate in the feed of rams at 1.0g/kg enhanced the efficiency of feed utilization and improved the semen quality positively.